Immune complexes-mediated activation of neutrophils in systemic lupus erythematosus is dependent on RNA recognition by toll-like receptor 8 - Wang, Ting; Kuley, Runa; Hermanson, Payton; Chu, Peirou; Pohlmeyer, Christopher; Ravichandar, Jayamary Divya; Lopez, David; Min-Oo, Gundula; Crellin, Natasha; Shang, Ching; Lood, Christian (Frontiers in Immunology, 2024)
IntroductionNeutrophil activation is important in systemic lupus erythematosus (SLE). We previously demonstrated that ribonucleoprotein (RNP) immune complexes (ICs) promoted neutrophil activation in a TLR7/8-dependent manner. However, it remains unclear if this mechanism occurs in patients. Here, we investigated the role of RNA recognition by evaluating TLR7/8 in plasma-mediated neutrophil activation in SLE.MethodsPlasma levels of neutrophil activation markers and ICs were measured by ELISA and flow cytometry in SLE patients (n=151) and healthy controls (HCs, n=31). Neutrophils were incubated with plasma and assessed for CD66b and CD11b up-regulation by flow cytometry in the presence of select inhibitors to define the mechanisms of neutrophil activation by SLE plasma.ResultsSLE plasma induced higher levels of CD66b (p=0.0002) and CD11b (p=0.01) expression than plasma from HCs. Blocking FcγRIIA, targeting RNA sensing by adding RNase, or blocking TLR7/8, TLR8 only, or IRAK4, decreased plasma-mediated neutrophil activation (p<0.05). Consistent with the ability of selective TLR8 inhibitor to block plasma-mediated neutrophil activation, TLR8 agonists, but not TLR7 agonists induced robust neutrophil activation. Further, neutrophil mRNA expression of TLR8 was higher than TLR7. Finally, patients with plasma samples inducing neutrophil activation in RNA-dependent manner had increased levels of interferon alpha, IP-10 (p<0.05), ICs (p<0.05), and reduced complement C3 levels (p<0.01), indicative of IC-driven disease.ConclusionThe data support IC-driven RNA-sensing by TLR8 in neutrophils is a key mechanism of neutrophil activation in SLE. Patients with elevated neutrophil activation and presence of RNA-containing ICs, may benefit from TLR8 inhibition and other strategies targeting RNA removal.